Malagasycoelum dracula gen. and sp. nov., a new genus and a new species of the subfamily Mirinae (Hemiptera: Heteroptera: Miridae) from Madagascar - Kim, Junggon; Roca-Cusachs, Marcos; Lim, Jongok; Jung, Sunghoon (Zootaxa, 2020)
Malagasycoelum dracula gen. and sp. nov. in Adelphocoris-Creontiades-Megacoelum complex is described from Madagascar. Morphological information of the new genus and new species is presented with photographs and illustrations.